Development of a hydrological index for mangrove in Matang Mangrove Forest Reserve, Peninsular Malaysia - Nik Zaidin, Nik Harun Al-Rashid (2017)
Mangrove hydrology is threatened by the massive degradation resulted from anthropogenic impacts such as rapid development and other land uses over the years. This study was implemented to characterize the climate and hydrological conditions with the seasonal and tidal variations and further developed an index to assess the mangrove hydrological conditions using Principal Component Analysis (PCA). Climate data were acquired from the Malaysian Meteorological Department (MetMalaysia) from 1989 to 2014 and the Department of Irrigation and Drainage (DID) from 1995 to 2014. Water samples from 24 sampling stations were collected from four rivers (Sg Tiram Laut, Sg. Jarum Mas, Sg. Tinggi, and Sg. Sepetang) representing three areas of Matang Mangrove (i.e. Kuala Trong, Sungai Kerang, and Kuala Sepetang) during the dry period (June and July) and the wet period (November and December) of 2015. In-situ data collection (DO, pH, EC, turbidity, TDS, salinity, temperature, river width, depth, and velocity) and laboratory analysis of TSS were conducted according to Standard Methods (APHA, 2012). Results from the climatic data analysis showed that the period 1999 to 2000 recorded the highest total rainfall for all sampled stations. Bukit Larut recorded the highest average annual rainfall (4,008.3 mm in 1999), and highest total rainfall (5,244 mm in 1999). Range for parameters in all sampled rivers were as follows: DO (0.16–12.36 mgL-1), temperature (26.70–32.90 °C), pH (6.21–9.81), EC (0.50–468.10 μScm-1), TDS (0.06–57.30 gL-1), salinity (0.10–32.33 ppt), turbidity (2.29–819.00 NTU), and TSS (0.10–41.70 mgL-1). Based on the PCA analysis, two of the parameters came out as important metrics for Mangrove Hydrology Index (MHI) which were TDS (score = 0.50) and salinity (score = 0.50). Findings from this study exhibited that the activities adjacent to the Matang Mangrove rivers, such as aquaculture, agriculture, and tourism contributed to the water quality dynamics, particularly TDS and salinity. Thus, the Mangrove Hydrological Index formulated might be able to benchmark the hydrology conditions and acts as a guideline for future land uses in mangrove.